Investigating students' perceptions of cognitive presence in relation to learner performance in blended learning courses: A mixed-methods approach - Almasi, Mustapha; Zhu, Chang (Electronic Journal of e-Learning, 2024)
A research article submitted to the Electronic Journal of e-Learning, Vol.18, No.4 of 2020, p324-336 .